2020
DOI: 10.17977/um060.2020v1p022-031
|View full text |Cite
|
Sign up to set email alerts
|

Holistic Practice of Fiqh Al-Muamalat: Halal Accountability of Islamic Microfinance Institutions

Abstract: This study aims to discover the practice of fiqh al-muamalat (Islamic law of transaction following Islamic fiqh) as a sharia-compliant, primarily the halal accountability of Islamic microfinance institutions Baitul Maal wa Tamwil (BMT) UGT Sidogiri Indonesia. This research used a descriptive, explanatory design with a holistic single-case design focus and was conducted from 2019 to 2020. For the data collection process, in-depth interviews were conducted with the informants. The data were analyzed using an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
(19 reference statements)
2
5
0
Order By: Relevance
“…The aim is to raise awareness of the ethical dimensions of the economy and businessso that the wealth obtained is halal and blessed through an ethical transaction. What has been stated by the management has strengthened the results of the previous research and showed that Islam does not just let an employee work as he/she wishes to achieve the objectives and wishes and justifies any means such as gambling, cheating, usury, and other vanities and must pay attention to moral and halal responsibilities (Muhammad, 2020;Sachedina, 2001). However, in Islam, there is a separation between what is permissible and what is not, the right and wrong and the lawful and the unlawful, and this is the ethics of Islam.…”
Section: Islamic Ethics Responsibilitymentioning
confidence: 66%
“…The aim is to raise awareness of the ethical dimensions of the economy and businessso that the wealth obtained is halal and blessed through an ethical transaction. What has been stated by the management has strengthened the results of the previous research and showed that Islam does not just let an employee work as he/she wishes to achieve the objectives and wishes and justifies any means such as gambling, cheating, usury, and other vanities and must pay attention to moral and halal responsibilities (Muhammad, 2020;Sachedina, 2001). However, in Islam, there is a separation between what is permissible and what is not, the right and wrong and the lawful and the unlawful, and this is the ethics of Islam.…”
Section: Islamic Ethics Responsibilitymentioning
confidence: 66%
“…Due to human resource constraints, even the risk of Sharia compliance, which is recognized as a unique risk for Islamic financial institutions, has not been fully implemented. Sharia compliance is not only seen as a requirement for business operational systems, but must also be implemented so that it becomes a work culture and ensures halal business transactions (Muhammad, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the application of religious and cultural values is essential in sustainable and ethical halal business. In fact, an Islamic understanding of laws is also crucial for businesspeople, including the law of the products being transacted, the transaction process, and the purpose of ensuring the halal business process [18]. In addition, the internalization of moral axioms leads to efficient and ethical businesses [19] if accompanied by a solid commitment to Islamic ethics [20].…”
Section: Introductionmentioning
confidence: 99%